The Efectiveness of Implementation Round Robin Technique in The Teaching of Writing for The Third Semester PBI Students of Pancasakti University Academic Year 2015/2016 - Nur Laila Molla (Cakrawala: Jurnal Pendidikan, 2016)
The objective of this research is to find out correlation whether Round RobinTechnique is effective to use in the teaching of writing for the third semester PBIstudents of Pancasakti University academic year of 2015/2016.The population of this research is the third semester PBI students of PancasaktiUniversity academic year of 2015/2016. The number of population is ninety fivestudents from five classes. This research is conducted by using two group designs;the first group is called experimental group that is taught using Round RobinTechnique, while the second group is called control group that is taught using FourSquare Technique. The sample is taken by using cluster random sampling. Eachgroup of samples consists of 30 students.The instrument used in this research is writing test in the form of guided. The test isconducted after the two groups get treatment for 4 meetings. The test is carried outto find out whether students who are taught by using Round Robin Technique get abetter writing score achievement than students who are taught using Four SquareTechnique. Then, the writing test is assessed by using rubric of Brown's writingscoring.Data analysis of this research is tested by using t-test in order to find out whetherthe research hypothesis is accepted or not. Based on the computation, the t-ratio is3.443. It is consulted with t-table on the significant level (a) of 5% and the degreeof freedom (df) is 58. The t-table obtained is 1.672. It shows that t-ratio is higherthan t-table (3.443 > 1.672), so the hypothesis of the research is accepted.The conclusion of this research is there is correlation between Round RobinTechnique and Writing Achievement. Students who are taught using Round RobinTechnique get a better writing achievement than students who are taught usingFour Square Technique. Round Robin Technique is proven to be one of the effectivetechniques to make students interested in learning writing and boost theachievement. It also makes the situation in the classroom more adaptable, so itprevents the students from getting bored.English teachers are suggested to apply Round Robin Technique in the teaching ofwriting. They should also motivate their students to work as a team to makelearning writing more fun. Furthermore, it is better for teachers to give theirstudents more and more writing assignments and evaluations to make themaccustomed to writing and also achieving higher academic score